2015
DOI: 10.4102/phcfm.v7i1.835
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical alternative intraosseous infusion site in severely hypovolemic children

Abstract: BackgroundStudies have shown that the venous system tends to collapse during hypovolemic shock. The use of the bone marrow space for infusions is an effective alternative, with the tibial insertion site being the norm.ObjectivesThis study was conducted to determine a quick intraosseous infusion method that could be an alternative to the tibial route in neonates during emergency situations.MethodA sample of 30 neonatal cadavers was dissected to explore a possible alternative to the tibial insertion site. The ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
7
0
3
Order By: Relevance
“…It has already been shown that, if the IO needle is inserted in the supero-lateral aspect of the humerus in supine position in neonatal cadavers, this area is a safe alternative access point for emergency infusions 16 without the risk of damage to vulnerable anatomical structures. We verify these results by showing the unhindered drainage of the contrast medium with adequate osseous proportions.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been shown that, if the IO needle is inserted in the supero-lateral aspect of the humerus in supine position in neonatal cadavers, this area is a safe alternative access point for emergency infusions 16 without the risk of damage to vulnerable anatomical structures. We verify these results by showing the unhindered drainage of the contrast medium with adequate osseous proportions.…”
Section: Discussionmentioning
confidence: 99%
“…Inserting a needle into the (tibial) bone allows a quick drug administration to the IO blood vessel system even during compromised circulation and shock. Cadaveric studies reported that IO needle position (i.e., humerus and proximal tibia) is feasible with both a semiautomatic battery-driven drill and manually inserted needles [97, 98]. A recent systematic review identified observational and simulation studies but no randomized trials [96].…”
Section: Vascular Accessmentioning
confidence: 99%
“…Em 1922, Drinker já propunha conforme estudos, o uso do acesso intraósseo em recém-nascidos e crianças, devido situações de riscos e procedimentos apropriados sem complicações. A tecnologia e estudos atuais permitem que a infusão em via intraóssea seja considerada a forma mais segura e eficaz, quando comparado com falhas ou impossibilidades de acessos intravenosos, centrais e umbilical (21) . Percebe-se a dificuldade da infusão devido a não inserção do acesso periférico (22) , ou mesmo a resistência devido ao calibre de pequeno Lúmen para um fluxo rápido (23) .…”
Section: Acesso Intraósseo Pediátricounclassified
“…Assim como é realizado o procedimento pediátrico, a utilização da via intraóssea nos adultos foi utilizada amplamente durante a segunda guerra mundial em 1940, caindo em desuso até a década de 1980,quando passou a ser usada novamente com mais frequência (21) , sendo que esta via proporciona um efeito significativo que é determinante em casos de suporte de vida avançado (27)(28) onde a inserção do acesso é feita através de ossos longos (úmero, tíbia, fêmur, esterno),que tem uma cavidade com maior concentração de medula óssea e não é constrita (21,(26)(27)(28) .…”
Section: Acesso Intraósseo No Adultounclassified
See 1 more Smart Citation